2022
DOI: 10.3390/nu14235068
|View full text |Cite
|
Sign up to set email alerts
|

Eating Habits and Body Weight Changes Induced by Variation in Smell and Taste in Patients with Previous SARS-CoV-2 Infection

Abstract: Olfactory and gustatory dysfunction are recognized as common symptoms in patients with COVID-19, with a prevalence ranging, respectively, between 41–61% and 38.2–49%. This review focused on relating the variations in dietary habits with the reduction/loss of smell and/or taste in patients who contracted the COVID-19 infection. Primarily, we reviewed the main pathological mechanisms involved in COVID 19-induced anosmia/dysosmia and ageusia/dysgeusia. Then, we explored and summarized the behavioural changes in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…This relationship was indirectly connected through the loss of appetite, suggesting that losing taste and smell sensations contribute to loss of appetite, which subsequently may result in weight loss. This observation aligns with prior research indicating that diminished appetite due to the loss of taste and smell precedes weight loss in individuals previously infected with COVID-19 (36). Identifying indirect relationships between symptoms offers insights into the co-occurrence of certain symptoms and potential strategies for alleviating their adverse effects.…”
Section: Discussionsupporting
confidence: 85%
“…This relationship was indirectly connected through the loss of appetite, suggesting that losing taste and smell sensations contribute to loss of appetite, which subsequently may result in weight loss. This observation aligns with prior research indicating that diminished appetite due to the loss of taste and smell precedes weight loss in individuals previously infected with COVID-19 (36). Identifying indirect relationships between symptoms offers insights into the co-occurrence of certain symptoms and potential strategies for alleviating their adverse effects.…”
Section: Discussionsupporting
confidence: 85%
“…A direct effect of SARS-CoV-2 on eating habits has not been clarified. However, some authors suggested that the transient alteration in taste and smell chemosensory receptors might play a role [50] in altered food intake. This may resolve quickly after acute infection, except for cases with persistent symptoms, showing a higher risk of eating-disorder development [51].…”
Section: Social Habits and Emotional Well-beingmentioning
confidence: 99%
“…Within the six research clusters, four clusters, including smell, anosmia, olfactory dysfunction, and recovery, are focused on OD and its related themes. Multiple studies have reported that the senses of smell and taste are the most frequently impacted in patients with neocoronary pneumonia, with OD and taste impairment being key symptoms of the illness (Lechien et al, 2020;Ferrulli et al, 2022). Among them, OD is classified into two levels: olfactory loss (anosmia) and olfactory decline (hyposmia).…”
Section: Emerging Themes From the Literaturementioning
confidence: 99%